فعالية استخدام نموذج العصا الناطقة في ترقية مهارة الكلام لدى تلاميذ الصف التاسع بمدرسة هداية الرحمن المتوسطة الإسلامية تانجيرنج - Rafli, Mochammad; Syamsul Arifin; Ubaid Ridlo (Penerbit Minhaj Pustaka, 2025)
The researcher chose this topic due to several issues in learning Arabic speaking skills: students face difficulties in learning Arabic, teaching focuses mainly on vocabulary, and teachers rarely use innovative methods. This study aims to determine the effectiveness of the Talking Stick method in improving speaking skills by comparing test results between students taught using role-play and those taught without the Talking Stick method. This quantitative research uses a quasi-experimental design with two groups: an experimental group using the Talking Stick method and a control group without it. The population consists of 80 ninth-grade students at Hidayaturrohman Tangerang Islamic Junior High School, with 40 students in each group. Data were collected through observation, interviews, and oral tests. Results show that the experimental group’s average score rose to 74.1, while the control group averaged only 9.95. The t-value (3.69) exceeded both the 5% (1.66) and 1% (2.37) significance levels, indicating the null hypothesis is rejected. Therefore, the Talking Stick method effectively enhances students’ speaking skills.